Of Cigarettes, High Heels, and Other Interesting Things - Danesi, Marcel (Springer, 2018)
Among species, human beings seem to be a peculiar lot. Why is it, for example, that certain members of the species routinely put their survival at risk by puffing on a small stick of nicotine? Why is it that some females of the species make locomotion difficult for themselves by donning high-heel footwear? Are there hidden or unconscious reasons behind such strange behaviors that seem to be so utterly counter-instinctual, so to speak? For no manifest biological reason, humanity has always searched, and continues to search, for a purpose to its life. Is it this search that has led it to engage in such bizarre behaviors as smoking and wearing high heels? And is it the reason behind humanity’s invention of myths, art, rituals, languages, mathematics, science, and all the other truly remarkable things that set it apart from all other species? Clearly, Homo sapiens appears to be unique in the fact that many of its behaviors are shaped by forces other than the instincts. The discipline that endeavors to understand these forces is known as semiotics. Relatively unknown in comparison to, say, philosophy or psychology, semiotics probes the human condition in its own peculiar way, by unraveling the meanings of the signs that undergird not only the wearing of high-heel shoes, but also the construction of words, paintings, sculptures, and the like.
An Introduction to Semiotics